Evaluation of an online medical teaching forum. (July 2014) - Ravindran, Rahul; Kashyap, Mavin; Lilis, Lydia; Vivekanantham, Sayinthen; Phoenix, Gokulan
Summary Background Social media is increasingly being used for teaching and assessment. We describe the design and implementation of a Facebook© teaching forum for medical students, and evaluate its effectiveness. Methods A Facebook© teaching forum was set up in a London Hospital to assist with learning and assessment for undergraduate medical students. An independent online survey was used to collate their experiences. Accessibility to the forum, usefulness in stimulating peer‐to‐peer discussion and the use of weekly formative assessments were evaluated using a Likert scale. Results In total, 91 per cent (n = 68/75) of students who had Facebook© joined the teaching forum. The majority of students completed the questionnaire (n = 39/68, 57%). All students visited the teaching forum group at least once a week. A significant proportion attempted all 10 question sets (n = 16/39, 41%). Students felt more comfortable asking questions in the forum than in ward rounds and clinics (n = 22/39, 56%). The general consensus was that Facebook© could be used for educational purposes, with just 5 per cent of students (n = 2/39) thinking that Facebook© should only be used socially and with 92 per cent believing that the forum helped to achieve the learning objectives of the curriculum (n = 36/39). <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Social media is increasingly being used for teaching and assessment </boxed-text> Discussion Facebook© provides a safe environment for learning and discussion amongst medical undergraduates undergoing their clinical attachments. Furthermore, through formative assessments set by a medical educator, it provides a useful revision tool for summative assessments and reinforces knowledge learned through conventional teaching methods.